A certeza da incerteza - Bauman, Zygmunt (Percurso, 2011)
Realização: Andrea Carvalho, Bela M. Sister, Danielle Melanie Breyton, Deborah Joan de Cardoso, Silvio Hotimsky e Susan Markuszower. Tradução: Susan Markuszower Revisão: Caia Fittipaldi, Renato Mezan